2022
DOI: 10.48077/scihor.25(8).2022.85-105
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics оf Transparency оf Ukrainian Banking Institutions Using Multivariate Analysis Methods

Abstract: Due to the imperfect state of transformations in the financial system of Ukraine and the banking sector, there is a steady tendency to increase the number of financially insolvent enterprises in various industries. This is especially true for the banking market, where considerable qualitative and quantitative changes have occurred recently. The purpose of this study is to investigate the problem of managing the of banking institutions by diagnosing the transparency level of their activities. The research metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Changes in the financial sector considerably affect the development of a country and, specifically, the welfare of its citizens, and countries with more developed financial systems tend to have higher GDP growth rates. This is confirmed by G. Azarenkova et al (2022), who within the framework of their study evaluated the role of the development of the financial system as a whole. Scientists have shown that providing greater access to financial products and services to individuals and individual companies can significantly increase the efficiency of the economy and contribute to its growth.…”
Section: Discussionmentioning
confidence: 59%
“…Changes in the financial sector considerably affect the development of a country and, specifically, the welfare of its citizens, and countries with more developed financial systems tend to have higher GDP growth rates. This is confirmed by G. Azarenkova et al (2022), who within the framework of their study evaluated the role of the development of the financial system as a whole. Scientists have shown that providing greater access to financial products and services to individuals and individual companies can significantly increase the efficiency of the economy and contribute to its growth.…”
Section: Discussionmentioning
confidence: 59%